2000
DOI: 10.1016/s0304-3959(00)00353-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of a human orthologue of rat vanilloid receptor-1

Abstract: Capsaicin, resiniferatoxin, protons or heat have been shown to activate an ion channel, termed the rat vanilloid receptor-1 (rVR1), originally isolated by expression cloning for a capsaicin sensitive phenotype. Here we describe the cloning of a human vanilloid receptor-1 (hVR1) cDNA containing a 2517 bp open reading frame that encodes a protein with 92% homology to the rat vanilloid receptor-1. Oocytes or mammalian cells expressing this cDNA respond to capsaicin, pH and temperature by generating inward membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
5
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(225 citation statements)
references
References 29 publications
10
201
5
9
Order By: Relevance
“…Over-expression of human VR1 cDNA into human hembryonic kidney (HEK) 293 cells was carried out as described previously (Hayes et al, 2000). Cells were grown as monolayers in minimum essential medium supplemented with non-essential amino acids, 10% foetal calf serum and 0.2 mM glutamine, and maintained under 95%/5% O 2 /CO 2 at 378C.…”
Section: Cytosolic Calcium Concentration ([Ca 2+ ] I ) Assaymentioning
confidence: 99%
“…Over-expression of human VR1 cDNA into human hembryonic kidney (HEK) 293 cells was carried out as described previously (Hayes et al, 2000). Cells were grown as monolayers in minimum essential medium supplemented with non-essential amino acids, 10% foetal calf serum and 0.2 mM glutamine, and maintained under 95%/5% O 2 /CO 2 at 378C.…”
Section: Cytosolic Calcium Concentration ([Ca 2+ ] I ) Assaymentioning
confidence: 99%
“…A human embryonic kidney cell line stably expressing human TRPV1 (hTRPV1.HEK293 cells) was generated as described previously (Hayes et al, 2000). Cells were cultured on plastic tissue culture dishes in modified Eagles's medium with Earle's salts and supplemented with 10% fetal bovine serum, nonessential amino acids and 0.2 mM L-glutamine while being maintained under 5% CO 2 at 371C.…”
Section: Cloning and Expression Of Human Trpv1mentioning
confidence: 99%
“…Whole-cell patch-clamp experiments were performed according to standard methods, using an Axopatch 200B amplifier, as described previously (Hayes et al, 2000). Thick-walled borosilicate glass electrodes (GC120F10; Harvard Apparatus) having 1.5-4 MO resistance were used to record currents following drug application using an automated three-barrelled solution switching device (Warner Instruments SF-77B).…”
Section: Electrophysiological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Caterina and co-workers cloned TRPV1 from a rat sensory neuron cDNA library and showed that the receptor is expressed in both the dorsal root (DRG) and trigeminal ganglia (TG) [24]. TRPV1 has also been cloned from humans [25], guinea pigs [26], rabbits [27], mouse mice [28] and dogs [29].…”
Section: Trpvs: a Brief Overviewmentioning
confidence: 99%